Matrix model of inhomogeneous medium with circular birefringence in single scattering case - Savenkov, S.N.; Oberemok, Ye.A.; Yakubchak, V.V.; Barchuk, О.I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2009)
The paper is devoted to the analysis of light scattering by inhomogeneous
circular birefringent media in a single scattering case. The object under investigation is a
circular birefringent crystalline slab with surface inhomogeneity. For the analysis, we
derive the Mueller matrix model for this media and use Cloude’s coherency matrix
method. Sample calculations are given for quartz SiO₂ and paratellurite TeO₂ .